2002
DOI: 10.1038/sj.bmt.1703570
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload might increase transplant-related mortality in haematopoietic stem cell transplantation

Abstract: Summary:Iron overload (IO) is associated with free radical generation and tissue damage. Our main objective was to ascertain if very high levels (VHL) of ferritin (у3000 g/l) and transferrin saturation (TS) у100% during conditioning had an impact on overall survival (OS) and transplant-related mortality (TRM) after a haematopoietic stem cell transplantation (HSCT). Levels of ferritin and TS were measured at days ؊7 and ؊4, respectively, in 25 patients who underwent HSCT after CY/TBI. The group consisted of 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 14 publications
5
94
4
Order By: Relevance
“…Disease duration before transplantation or iron overload has been regularly found to increase NRM and sometimes decrease survival in bone marrow or peripheral blood transplant recipients. [33][34][35][36] Our study confirmed that RIC before UCBT is associated with a reduction in NRM, as observed in unrelated HSCT recipients. 36 Despite poorer general conditions and high-risk MDS, patients who received RIC had decreased NRM and a trend toward better DFS.…”
Section: P-valuesupporting
confidence: 76%
“…Disease duration before transplantation or iron overload has been regularly found to increase NRM and sometimes decrease survival in bone marrow or peripheral blood transplant recipients. [33][34][35][36] Our study confirmed that RIC before UCBT is associated with a reduction in NRM, as observed in unrelated HSCT recipients. 36 Despite poorer general conditions and high-risk MDS, patients who received RIC had decreased NRM and a trend toward better DFS.…”
Section: P-valuesupporting
confidence: 76%
“…These results were in concert with earlier studies that reported the clinical relevance of iron overload with TRM and survival. 7,8 A recent study reported a strong association of elevated serum ferritin level with lower OS and diseasefree survival in HSCT patients, and this association was restricted to patients with acute leukemia or myelodysplastic syndrome. 8 We did subgroup analysis with the patients other than acute leukemia or myelodysplastic syndrome and found that TRM of the F41000 group (50%) was higher than those of Fo1000 group (6.7%) and IC group (0%), but this was not statistically significant (P ¼ 0.060).…”
Section: Discussionmentioning
confidence: 99%
“…Free iron catalyzes the conversion of reactive oxygen species intermediates to highly toxic-free radicals, which may mediate tissue injury. 2 Recent studies have shown that iron overload is related to hepatic complications, 3 infectious complications [4][5][6] and survival 7,8 in HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…Iron overload has been associated with increased susceptibility to organ damage and increased risk of infection [14,15]. Patients undergoing HSCT often have received multiple blood transfusions prior to transplantation, which probably contribute to elevated ferritin levels.…”
Section: Discussionmentioning
confidence: 99%